2021
DOI: 10.3389/fcvm.2021.736226
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exosomes at the Late Phase of Remote Ischemic Pre-conditioning Attenuate Myocardial Ischemia-Reperfusion Injury Through Transferring miR-126a-3p

Abstract: Background: Remote ischemic pre-conditioning (RIPC) alleviated the myocardial ischemia-reperfusion injury, yet the underlying mechanisms remain to be fully elucidated, especially at the late phase. Searching a key component as a transfer carrier may provide a novel insight into RIPC-mediated cardioprotection in the condition of myocardial ischemia-reperfusion.Objective: To investigate the cardioprotective effect of plasma exosomes at the late phase of RIPC and its potential signaling pathways involved.Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Giricz et al showed for the first time that exosomes isolated from hearts played a protective role in myocardial I/R injury by the transmission of RIPC signal [ 7 ]. Moreover, Li et al [ 8 ] showed that exosomes released from RIPC plasma were crucial in mediating cardioprotective effects through transferring miR-126a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Giricz et al showed for the first time that exosomes isolated from hearts played a protective role in myocardial I/R injury by the transmission of RIPC signal [ 7 ]. Moreover, Li et al [ 8 ] showed that exosomes released from RIPC plasma were crucial in mediating cardioprotective effects through transferring miR-126a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…The initial activation of the autophagosome during the first window of protection alleviates the damage of I/R injury and supports cell function by clearing damaged protein aggregates, by removing damaged ROS-producing mitochondria and through the recycling of macromolecules for use in cell repair [ 88 ]. A study of exosomes from rats has shown that this response may appear as long as 48 h after the RIC stimulus [ 89 ]. Preservation of post-ischemic cardiac function, measured by post-ischemic LV end-diastolic and developed pressure, is similar by acute, delayed and repeated RIC in experimental studies of rats and mice [ 88 , 90 , 91 ].…”
Section: Cardioprotection – Attenuation Of Myocardial Ischemia/reperf...mentioning
confidence: 99%
“…In addition, RIPC‐induced production of plasma exosomes can reduce apoptosis and myocardial I/R injury by paracrine transfer of miR‐24 155 . Moreover, plasma exosomes in late RIPC can reduce myocardial I/R injury through exosomal miR‐126a‐3p 156 . Furthermore, miR‐342‐3p dysregulation in plasma exosomes during early recovery after AMI may cause impaired cardiac protective potential.…”
Section: Evs Derived From Different Cell Types Promote the Treatment ...mentioning
confidence: 99%
“… 155 Moreover, plasma exosomes in late RIPC can reduce myocardial I/R injury through exosomal miR‐126a‐3p. 156 Furthermore, miR‐342‐3p dysregulation in plasma exosomes during early recovery after AMI may cause impaired cardiac protective potential. By targeting SOX6 and transcription factor EB ( TFEB ), miR‐342‐3p can enhance exosome‐mediated repair of cardiac injury by suppressing myocardial apoptosis and autophagy.…”
Section: Evs Derived From Different Cell Types Promote the Treatment ...mentioning
confidence: 99%